A new self-assessment teaching assistant survey for growth and development - Mewis, Keith; Dee, Jaclyn; Lam, Vivienne; Obradovich, Shannon; Cassidy, Alice (Teaching and Learning Inquiry, 2018)
During their time as Teaching Assistants (TAs), graduate students develop a variety of skills, knowledge, and attitudes, based on teaching and related facilitation experiences. As TAs move on to future opportunities, their prior experiences form a foundation upon which additional teaching experience builds. Presently, there are few tools to gauge pedagogical growth during graduate student involvement as TAs in a specific post-secondary course, or as a consequence of their participation in a specialized TA training or teaching program. We created a model for TA development in SCIE 113 (First-year Seminar in Science) at the University of British Columbia. Based on this model, we designed a new survey for TAs to self-assess skills, knowledge and attitudes that they bring with them from prior experience, and those that they develop or further during their time as a TA in SCIE113. We administered the survey to 18 current and past SCIE 113 TAs as of December 2015, representing the complete population of TAs. The results showed that SCIE 113 TAs with similar levels of experience shared similar skills, knowledge, and attitudes as assessed by this survey. Those TAs with the most experience had greater abilities in roles previously identified as unique to the course. Others working with graduate students can use or adapt the survey questions to investigate and stimulate the growth of TAs in their course or program.